THE EFFECT OF USING DIGITAL GAME-BASED LEARNING METHOD THROUGH MATHPLAYGROUND TO IMPROVE STUDENT LEARNING OUTCOMES IN MATH SUBJECT AT AVICENNA GEMILANG ELEMENTARY SCHOOL - Septiara Giva Asmara; Donald Samuel Slamet Santosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of using digital game-based learning methods to improve student learning outcomes in mathematics subject at Avicenna Gemilang Elementary School using mathplayground as the learning media. This research uses an experimental method with one group pretest posttest design. The samples used in this study were 25 grade one students in Avicenna Gemilang Elementary School. The data collection of this study was with a test instrument in the form of a multiple-choice question test given at the beginning and end of learning. Data analysis was carried out based on quantitative data by calculating the average pretest and posttest. To find out if there is a significant increase, the researcher conducted a normality test, and t test, namely paired sample test with the assistance of SPSS 26. The results of this study showed that the average pretest student score was 64.40 and posttest 76.80 and the results of the paired sample test data analysis showed a sig. (2-tailed), 0 < 0.05 (0.000 < 0.05). Therefore, it can be concluded that there is an effect of using digital game-based learning methods to improve student learning outcomes in math subjects at Avicenna Elementary School using mathplayground.